MEASUREMENT OF HAFNIUM AND ZIRCONIUM IN ZIRCONIUM ORES: OUTCOME OF A NATIONAL INTERCOMPARISON EXERCISE, ZH-A - Siddique, N.; Waheed, S.; Rahman, A.; Ahmad, S.; Qureshi, I. H. (The Nucleus, 2020)
A case study is presented in this paper in which a Zirconium pilot plant was set up for the production of zirconium for the cladding of fuel rods. Hafnium occurs in combination with zirconium and is a neutron absorber. Therefore, its concentration has to be kept within tolerance limits and monitored throughout the production process. Five Pakistan Atomic Energy Commission (PAEC) laboratories using different techniques measured the concentrations of Zr and Hf with a wide range of results, i.e. more than three times the standard deviation. Therefore, a national intercomparison exercise, ZH-A was conducted to remove discrepancies and improve analytical procedures in the measurement of hafnium and zirconium in zirconium ores. The ZH-A series of reference samples, prepared at the Pakistan Institute of Nuclear Science and Technology (PINSTECH), were used for this purpose. It was observed that the measurement errors decrease with an increase in Hf concentration ( 298 ppm to 1.75%) for all techniques used in this exercise. This was especially significant for Atomic Absorption Spectrometry (AAS). Measurement errors for Hf using AAS are also the highest. Neutron activation analysis (NAA) was found to be the most reliable of all the tested techniques for the measurement of both Hf and Zr in zirconium ores due to its high sensitivity and accuracy.